Transforming From Traditional To E-intermediary: A Resource Orchestration Perspective. Issue 3 (3rd July 2021) - Cui, Miao; Li, Xin; Kamoche, Ken
ABSTRACT: The development of digital technologies has forced an increasing number of traditional intermediaries to transform into e-intermediaries for survival. This study adopts the resource orchestration perspective to investigate the digital transformation process and mechanism by using a case study method. Our findings indicate that the digital transformation of intermediaries requires a fit among the strategic logic, resource orchestration, and capability and reveal the roles of information technology and strategic logics in the transformation process. This study contributes to theory-building in digital transformation by providing a comprehensive framework for reconfiguring organizational resources and capabilities to cope with the requirements of e-intermediaries. Our findings also provide useful managerial insights for intermediaries in terms of resource-focused actions and resource portfolios to bridge supply and demand.